2004
DOI: 10.1093/jn/134.8.2004
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Isothiocyanates Inhibit the Growth of Human Bladder Carcinoma Cells

Abstract: Many isothiocyanates (ITCs), some of which are abundant in cruciferous vegetables, have been repeatedly shown to inhibit carcinogenesis in a variety of rodent organs. However, several naturally occurring ITCs also promoted bladder tumorigenesis in rodents, raising the question of whether ITCs behave differently in bladder cells. Alternatively, the observed carcinogenic effects of ITCs may result from prolonged exposure of the bladder epithelium, where the tumors originate, to high concentrations of electrophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
82
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(93 citation statements)
references
References 44 publications
10
82
1
Order By: Relevance
“…We previously showed that several isothiocyanates, including sulforaphane, induced apoptosis and cell cycle arrest in this cell line (17). Our current results show that the broccoli sprout extracts impart potent antiproliferative activity and that such activity depends almost entirely on the enzymatic conversion of glucosinolates to isothiocyanates.…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…We previously showed that several isothiocyanates, including sulforaphane, induced apoptosis and cell cycle arrest in this cell line (17). Our current results show that the broccoli sprout extracts impart potent antiproliferative activity and that such activity depends almost entirely on the enzymatic conversion of glucosinolates to isothiocyanates.…”
Section: Introductionsupporting
confidence: 65%
“…Sulforaphane was previously shown to induce apoptosis of UM-UC-3 cells at 7.5 to 30 Amol/L, which was associated with mitochondrial damage, cytoplasmic relocation of cytochrome c, cleavage/activation of caspase-9 and caspase-3, as well as cleavage of poly(ADP-ribose)-polymerase (17,23). The isothiocyanates in broccoli sprout extracts behaved similarly.…”
Section: Induction Of Apoptosis By Broccoli Sprout Isothiocyanate Extmentioning
confidence: 90%
“…15,53 Dietary exposure of DITC in the post-initiation phase decreased BrdU-LI and cyclin D1 positive cell ratios in urinary bladder tumors, but did not significantly reduce the development of urinary bladder tumors. Recently, Tang and Zhang 54 found that ITC blocked cell-cycle progression and downregulated several cellcycle regulators in human bladder carcinoma cells in certain concentration. The cytostatic activity of DITC in promotion phase was lower than that in initiation phase.…”
Section: Discussionmentioning
confidence: 99%
“…Bladder cancer is particularly interesting because dietary isothiocyanates, a group of key anticarcinogens occurring in cruciferous vegetables, show potent chemopreventive effects against bladder cancer in both in vitro and in vivo models (4)(5)(6)(7)(8)(9). Moreover, the unique in vivo pharmacokinetics and disposition of orally ingested isothiocyanates in humans renders the bladder the best targeted organ for the anticancer effect of dietary isothiocyanates (5).…”
Section: Introductionmentioning
confidence: 99%